2009
DOI: 10.3928/01484834-20090518-01
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Instruction: Using the Strengths-Based Approach with Nursing Students

Abstract: Clinical instruction experience can vary significantly based on the needs of the organization and the individual characteristics of instructors and students. Clinical instructors may encounter difficulties in their relationships with students, such as personality conflicts, differences in style and values, and limited skill levels or a lack of interest on the part of students. To reduce obstacles when working with challenging students, a strengths perspective approach is recommended. This framework emphasizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 10 publications
3
31
0
2
Order By: Relevance
“…Gaberson and Oermann (2007) described a model of strengths based on interaction between clinical instructors and students. The strengths aspect is a practical approach that enables flexible working relationships based on principles of self-regulation, empowerment, reciprocity, cooperation, and reflecting http: //dx.doi.org/10.15405/epsbs.2018.06.6 Corresponding Author: Neomi Dar Cohen Selection and peer-review under Clinical instructors must recognize and appreciate students' beliefs, previous experiences, and their fears, so as to help them formulate good outcomes, both in their relationships with patients, and in their personal growth as nurses (Cederbaum & Klusaritz, 2009). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Gaberson and Oermann (2007) described a model of strengths based on interaction between clinical instructors and students. The strengths aspect is a practical approach that enables flexible working relationships based on principles of self-regulation, empowerment, reciprocity, cooperation, and reflecting http: //dx.doi.org/10.15405/epsbs.2018.06.6 Corresponding Author: Neomi Dar Cohen Selection and peer-review under Clinical instructors must recognize and appreciate students' beliefs, previous experiences, and their fears, so as to help them formulate good outcomes, both in their relationships with patients, and in their personal growth as nurses (Cederbaum & Klusaritz, 2009). …”
Section: Literature Reviewmentioning
confidence: 99%
“…These include but are not limited to clearly outlining performance criteria for evaluation, [1,2] insuring that students clearly understand the difference between input on clinical learning and summative evaluation of their overall success or failure, [6] providing input on students' learning needs or expectations [5] and accomplishments including their strengths in a positive way to enhance their performance, [7] motivating, [8][9][10][11][12] empowering, [13,14] and bringing about desired behavioral changes needed to work independently and as a team player in a clinical group. Clinical educators need to develop innovative ways to overcome these considerable challenges and continue to make an effort to develop partnerships with students that promote effective interpersonal relationships.…”
Section: Introductionmentioning
confidence: 99%
“…A technique to incorporate the strengths perspective in a way that is "empowering" is to offer students the opportunity to lead a session using skills and knowledge from the practice setting. [9] Furthermore, evidence suggested that empowered students tend to be successful in school and after graduation. [23] Since this learning activity is open and self-directed, learners are able to use this opportunity to facilitate their own learning goals, which may include practice for the National Council Licensure Examination (NCLEX).…”
Section: An Open Self-directed Curriculum Designmentioning
confidence: 99%
“…A study using a strengths-based approach in clinical teaching suggested that this approach promotes student empowerment, collaborative learning, and mutual growth. [9] Informed by experiences of this study, we explored the design and implementation of a strengths-based activity during clinical reflection seminars.…”
Section: Theoretical Frameworkmentioning
confidence: 99%